A muted El Niño-like condition during late MIS 3. (15th February 2021) - Yamoah, Kweku A.; Chabangborn, Akkaneewut; Chawchai, Sakonvan; Fritz, Sherilyn; Löwemark, Ludvig; Kaboth-Bahr, Stefanie; Reimer, Paula J.; Smittenberg, Rienk H.; Wohlfarth, Barbara
Abstract: The evolutionary dynamics of El Niño Southern Oscillation (ENSO) over the last glacial period remains understudied, despite its potential in providing a "cold case" for climate sensitivity studies. Here, we investigate SE Asian-Pacific paleoclimate records to decipher the dominant underlying mechanism that governed tropical Asian-Pacific hydrology during MIS 3. Our results suggest that the glacial emergence of the Sunda Shelf likely altered the atmospheric circulation pattern in Southeast (SE) Asia and led to the realignment of rainfall patterns between Thailand and Indonesia during the last glacial period. We also propose that the long-term hydrological regime change in the tropical Asian-Pacific region during MIS 3 was mainly influenced by an El Niño-like mechanism. An intense El Niño-like condition led to strong aridity in SE Asia during mid MIS 3. By late MIS 3, an enhanced seasonality dampened the intensity of the El Niño-like conditions, thus, leading to muted aridity in SE Asia. The alternating warm and wet summer months and droughts during winter favoured the proliferation of C4 plant types in Northern Thailand from mid MIS 3 to late MIS 3. Highlights: Emergence of the Sunda Shelf altered precipitation patterns in Southeast (SE) Asia. El Niño-dominated climate governed the tropical Asian-Pacific region during MIS 3. Stronger El Niño-like conditions led to heightened aridity during mid MIS 3. Increasing seasonality dampened El Niño-like conditions in late MIS 3.